Preconditions, Regulatory Failure and Corporate Negligence Behind the Lac-Mégantic Disaster - Campbell, Bruce (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2018)
The Lac-Mégantic oil train disaster, July 6, 2013, was not a highly improbable, impossible-to-anticipate event. A number of prior conditions, the product of deliberate regulatory and corporate actions and inactions, contributed to the risk of a major accident. These preconditions include: three decades of railway deregulation under Conservative and Liberal governments under which railways gained increasing freedom to regulate themselves; a weakened, dysfunctional regulator and a flawed safety regime; a negligent company with repeated safety violations and penchant for cutting corners; a regulation-adverse , austerity-minded government indifferent to the growing dangers posed by the increase in the transportation of oil-by-rail; and an industry bent on blocking or weakening potential protective regulations affecting its costs. These preconditions provided the context for a series of mutually reinforcing regulatory failures, which accumulated, and as oil-by-rail grew, so too did the prospects of avoiding an accident diminish, to the point where the question became: when, where and how serious.